ANALISA PERHITUNGAN NILAI JUAL OBJEK PAJAK (NJOP) PADA USAHA PEMBUDIDAYAAN DAN PENANGKARAN IKAN AIR TAWAR (BANDENG) (Study Kasus Pada Tempat Budidaya Ikan Bandeng di Kabupaten Sidoarjo) - Johan Aria Lesmana (Universitas Trunojoyo Madura, 2013)
The objective of this research is to find out whether administration matter such as tax registration, tax reporting and tax payment has been in accordance with Undang-undang Nomor 12 Tahun 1994 about Land and Building Tax (Pajak Bumi dan Bangunan). This is a case study research with a unit analysis of a bandeng embankment at Banjar Kemuning Village, Sedati, Sidoarjo, East Java.Research found that the administration activities such as tax registration, tax reporting, and tax payment has been complied with Indonesian taxation law as there never been any taxation fine. However, there was still some discrepancy calculation of tax payable between the calculation of Kantor Pelayanan Pratama Sidoarjo Utara and embankment recalculation of Rp 86.140,00.